Relationship Between Mitochondrial Structure and Bioenergetics in Pseudoxanthoma elasticum Dermal Fibroblasts - Lofaro, Francesco Demetrio; Boraldi, Federica; Garcia-Fernandez, Maria; Estrella, Lara; Valdivielso, Pedro; Quaglino, Daniela (Frontiers in Cell and Developmental Biology, 2020)
Pseudoxanthoma elasticum (PXE) is a genetic disease considered a paradigm of ectopic mineralization disorders, being characterized by multisystem clinical manifestations due to progressive calcification of skin, eyes and the cardiovascular system, resembling an age-related phenotype. Although, fibroblasts do not express the pathogenic ABCC6 gene, nevertheless these cells are still under investigation because they regulate connective tissue homeostasis generating the “arena” where cells and extracellular matrix components can promote pathologic calcification and activation of pro-osteogenic factors can be associated to pathways involving mitochondrial metabolism. Aim of the present study was to integrate structural and bioenergenetic features to deeply investigate mitochondria of control and of PXE fibroblasts cultured in standard conditions, to explore their role in the development of the PXE fibroblasts’ pathologic phenotype. Proteomic, biochemical and morphological data provided new evidence that in basal culture conditions: 1) the protein profile of PXE mitochondria reveals a number of differentially expressed proteins whose changes indicate oxidative stress, altered oxidative phosphorylation and calcium homeostasis in addition to modified structure and organization; 2) measure of oxygen consumption indicates that PXE mitochondria have a low ability to cope with a sudden increased need for ATP via oxidative phosphorylation; 3) mitochondrial membranes are highly polarized in PXE fibroblasts and this condition contributes to increased ROS levels; 4) ultrastructural alterations in PXE mitochondria are associated with functional changes; 5) PXE fibroblasts exhibit a more abundant, branched and interconnected mitochondrial network compared to control cells indicating that fusion prevail over fission events. In summary, the present study demonstrates deregulated mitochondria in PXE fibroblasts. Since it has been observed that mitochondria are key players in the development of the aging process, that fibroblasts cultured from aged individuals or aged in vitro are more prone to calcify and that PXE can be also regarded as a premature-aging syndrome, it can be hypothesized that mitochondria represent a common pathway in the development of ectopic calcification in aging and in diseases. Therefore ameliorating mitochondrial functions and cell metabolism can open new strategies to positively regulate a number of signalling pathways associated to pathologic calcification.